2014
DOI: 10.1186/1750-2187-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple functions of G protein-coupled receptor kinases

Abstract: Desensitization is a physiological feedback mechanism that blocks detrimental effects of persistent stimulation. G protein-coupled receptor kinase 2 (GRK2) was originally identified as the kinase that mediates G protein-coupled receptor (GPCR) desensitization. Subsequent studies revealed that GRK is a family composed of seven isoforms (GRK1–GRK7). Each GRK shows a differential expression pattern. GRK1, GRK4, and GRK7 are expressed in limited tissues. In contrast, GRK2, GRK3, GRK5, and GRK6 are ubiquitously exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 112 publications
(152 reference statements)
1
67
0
Order By: Relevance
“…Growing evidence indicates that GRKs can exert different effects within the cell depending on the stimulus, cell type, and localization [97, 121]. In this sense, we were the first to demonstrate a mitochondrial localization for GRK2 [122], later confirmed by other investigators [123], establishing a functional role for GRK2 in organelle biogenesis and ATP production [122, 124].…”
Section: Introductionsupporting
confidence: 69%
“…Growing evidence indicates that GRKs can exert different effects within the cell depending on the stimulus, cell type, and localization [97, 121]. In this sense, we were the first to demonstrate a mitochondrial localization for GRK2 [122], later confirmed by other investigators [123], establishing a functional role for GRK2 in organelle biogenesis and ATP production [122, 124].…”
Section: Introductionsupporting
confidence: 69%
“…Subsequently, b-arrestins bind to the receptor, inhibiting further G protein activation by blocking receptor-G protein coupling [2]. In addition to the regulation of GPCR desensitization, it has recently been revealed that GRKs phosphorylate not only GPCRs but also non-GPCRs [3]. Furthermore, this phosphorylation leads to the regulation of GPCR-independent intracellular signaling pathways [4].…”
Section: Introductionmentioning
confidence: 98%
“…For instance, GRK2 is reported to phosphorylate p38 and impair MKK6-induced p38 activation [5]. Among 7 GRK subfamilies, the intracellular substrates for GRK2 and GRK5 have been well elucidated [3,4]. On the other hand, those for other GRKs are poorly understood.…”
Section: Introductionmentioning
confidence: 98%
“…Phosphorylation of the receptor by GRK2 recruits β-arrestin 2, leading to further receptor desensitization (41,42,43). β-Arrestin 2 binds to various regions of GPCR cytoplasmic tail domains and regulates endocytosis, frequently in response to GRK2-mediated receptor phosphorylation (44,45,46).…”
Section: Involvement Of Grk2 In G-protein-independent Signalingmentioning
confidence: 99%